Investigation of congenital tremor associated with Classical swine fever virus genotype 2.2 in an organized pig farm in north-eastern India - Barman, Nagendra Nath (Virusdisease, 2021)
The present study describes an outbreak of Classical swine fever (CSF) in an organized pig farm followed by an episode of CSF virus (CSFV) associated congenital tremors in piglets. The outbreak was recorded in a newly procured herd of Hampshire pigs housed adjacent to the existing pigs of the farm. The recorded CSF outbreak caused a mortality of 100% in the newly procured and 54.28% in the existing herd. As the disease subsides, the clinically recovered boars were served naturally with Tamworth gilts. Though, the sows farrowed on usual gestation period, litters born to each sow showed congenital tremors and eventually died within 24 h of birth. Necropsy analysis of affected piglets was indicative of CSFV infection and was further confirmed using RT-PCR signifying a transplacental infection. The CSFV strains from the initial outbreak and post outbreak episode of congenital tremors were successfully isolated in PK-15 cells and detected in indirect FAT and RT-PCR. Phylogenetic analysis based on E2 gene and 5′NTR of CSFV grouped the isolates within the genotype 2.2 and revealed close resemblance with previously reported Indian isolates of CSFV genotype 2.2 origin. To the best of our knowledge, this is the first report of CSFV induced congenital form reported from India under natural conditions.